Phase II trial of S‐1 treatment as palliative‐intent chemotherapy for previously treated advanced thymic carcinoma - Okuma, Yusuke (Cancer Med, 2020)
Thymic carcinoma (TC) is a rare cancer with minimal evidence of survival following palliative‐intent chemotherapy. Sunitinib, everolimus, and pembrolizumab have been proposed as active agents based on previous phase II trials. In this phase II study, TC patients previously treated with platinum‐based chemotherapy were enrolled. The patients received S‐1 orally twice daily at a dose of 40‐60 mg/m(2) for 4 weeks, followed by 2 weeks off until the progression of the disease or the presence of unacceptable toxicities. The primary endpoint was the objective response rate (ORR), and secondary endpoints were progression‐free survival (PFS), overall survival (OS), and safety. The sample size of 26 patients was planned to reject the ORR of 10% under the expectation of 30% with a power of 0.80 and a type I error of 0.05 (one‐sided). Twenty‐six patients were recruited between 2013 and 2016; 23 patients had squamous cell carcinoma and 10 had an ECOG performance status of 0. One patient showed complete response and seven patients showed partial responses, resulting in a 30.8% response rate (90% confidence interval [CI], 18.3‐46.9) and an 80.8% disease control rate (90% CI, 65.4‐90.3). The median PFS was 4.3 months (95% CI, 2.3‐10.3 months) and median OS was 27.4 months (95% CI, 16.6‐34.3). Adverse events of grade ≥ 3 included neutropenia (12%), skin rash (8%), elevated alanine aminotransferase, and fatigue (4%). No treatment‐related death was observed. S‐1 confirmed clinical activity with tolerability in patients with previously treated TC. (UMIN000010736).